ANALISIS PERSEPSI MASYARAKAT TERHADAP KUALITAS PELAYANAN KEPENDUDUKAN DAN CATATAN SIPIL KOTA TEGAL - Indah Manfaati Nur; M.Saifuddin Nur (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The study is focused on analysis of community perception on quality of population services and civil registration of Tegal city. Based on several analysis results above can be concluded that Gap analysis shows the overall gap mark is negative, meaning the quality of service at the Department of Population and Civil Registration has not reached the quality expected by the community. More specifically in the service indicator the service features that have the greatest coefficient on all service units. The average comparison test between the perception of service quality and the quality expectation of the community indicates that there is no significant difference, meaning that the quality of service provided with the expected quality of expectations by the community does not differ from the good of the service. The weighted average index value for the overall service unit is very good category, which means that in general all the services in the Department of Population and Civil Registry are assessed to have excellent perception quality by the people of Tegal City. Keywords:   Service Quality, Department of Population and Civil Registration, Tegal City